PEMANFAATAN GOOGLE CLOUD SPREADSHEETS PADA SISTEM MANAJEMEN DATA TOKO KACA DUA PUTRA - Mohd Fawwaz Ramadhan; Muhammad Rizkan; Rahmathidayatullah; Sri Astuti (Fakultas Ekonomi dan Bisnis, 2025)
This study discusses the design of a web-based data management system integrated with Google Cloud Spreadsheets to support the digitalization of MSME operations, especially at Toko Kaca Dua Putra. This system was developed using the Waterfall method and includes features for recording products, transactions, customers, and reports that are synchronized in real-time. The implementation results show increased efficiency, accuracy, and ease of data access. Integration with Google Sheets makes this system a practical and lightweight solution for MSMEs who want to transform digitally.